Transforming Student Learning: The Role of Digital Library Utilization and the Quality of Digital Collections on Performance and Learning Outcomes with Information Literacy Moderation - Retno Danu Rusmawati; Wawan Gunawan; Irwan Alnarus Kautsar; Zulidyana Dwi Rusnalasari (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The transformation of learning in higher education places digital libraries beyond simply providing information access, but rather as strategic instruments that determine the quality of student performance and learning outcomes. This study aims to comprehensively examine the influence of digital library use and the quality of digital collections on student performance and learning outcomes, with information literacy as a moderating variable. The study used a quantitative approach with an explanatory design using the Structural Equation Modeling method on 200 students of the Graduate School of PGRI Adi Buana University Surabaya, intakes of 2023 to 2025. Data were collected using a Likert-scale questionnaire and analyzed using measurement and structural models to test the direct and indirect effects between variables. The results showed that the quality of digital collections significantly influenced student learning outcomes and information literacy, while the use of digital libraries had no direct effect on student performance. Information literacy was shown to have a very strong influence on student performance and played a significant role in mediating the influence of the quality of digital collections and the use of digital libraries on performance and learning outcomes. These findings provocatively emphasize that access and intensity of digital library use will be meaningless without adequate information literacy, thus information literacy emerges as a determining factor that transforms the quality of digital library resources and utilization into tangible academic achievements. This research provides theoretical contributions in strengthening the integrative model of digital library-based learning as well as practical implications for higher education administrators to shift the policy focus from merely technology development to strengthening the quality of collections and student information literacy in a sustainable manner.